BENEFITS OF ENGAGING IN DEBATES FOR ENGLISH AS A SECOND LANGUAGE LEARNERS - Mamatursunova Marhabo G'ulomjon kizi; Yuldasheva Mehriyo Sa'dullo kizi; Egamberdiyeva Iroda Abdurahimovna (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article explains extremely indispensable profits of debate in order to provide people who is learning foreign language to speak fluency and this article try to stop ESL to play ineffective game such as following games.